(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: the disorder of neuron system by the action of hyperglycemia is Diabetic neuropathy considers a common diabetic complication which is associated with a wide scope of clinical cases. Peripheral neuropathy (PN) represents a clinical case, wherein the peripheral nervous system is damaged. Accordingly, biochemical parameters have importance to apply as good predictor factors. Accordingly we attempt to assess the biochemical factors of Neuron Specific Enolase NSE, Calpotectin CALP, Xanthine Oxidase XOD in patients suffering from this type of diabetes complications as early predictors and study their correlations. Methods: Fifty eight patients are known to have diabetic mellitus, which is classified into three groups. Group I represents DPN of 30 patients, group II referred to 28 diabetic patients without DPN, in addition to 30 healthy subjects as a control group, with range age (38-70) years old. BMI was determined for all the studied groups. Levels of FBS, lipid categories and HbA1C were estimated. NSE, CALP and XOD levels were measured by ELISA method. hs-CRP also determine for patients and control. Results: The results revealed that levels of both FBS and HbA1C are increased significantly (p<0.05) in both patients groups rather than healthy subjects. Moreover, results recorded an important increase of cholesterol, TGs, LDL and VLDL levels (p<0.05). in contrast the HDL decrease in the two patient groups related to healthy group. Increased levels of NSE, CALP, XOD and hs-CRP in DPN group and diabetic group compared with control group. The results of this study showed a direct correlation between BMI and FBS, in addition to BMI and hsCRP which possess the same correlation. Analysis by ROC curve showed that both NSE and CALP are representing the strongest markers for diagnosis of diabetic neuropathy followed by XOD and hs-CRP respectively. Conclusion: Levels of the studied factors consider good indicators to use them as suitable markers for early detection of diabetic sensory neuropathy. The results of ROC curve analysis revealed that NSE and CALP is the strongest biomarker for diagnosis of diabetic neuropathy.